Structural and functional properties of the glycosylated products of perilla seed meal proteins - WANG Dan; LI He; ZHANG Zhijun; LI Huizhen (浙江大学学报. 农业与生命科学版)
Fructose (FRU), dextran (DEX), and maltodextrin (MD) with different molecular weights were used as inducers to modify perilla seed meal protein (PSMP) using a wet heating method, in order to explore their effects on the structural and functional properties of PSMP glycosylated products. The detection results of grafting degree and browning degree showed that all three kinds of sugars underwent glycosylation reactions with PSMP. Compared with PSMP, the solubility of the three PSMP glycosylated products was improved under medium and alkaline conditions, with the solubility of P-DEX showing an increase of about 9% at pH 7.0. Meanwhile, the emulsifying, foaming, thermal properties, and oil-holding capacity of the three PSMP glycosylated products were significantly improved, with P-DEX showing the best performance. The detection results of Fourier transform infrared spectrum (FTIR) and endogenous fluorescence spectra confirmed that both the secondary and tertiary structures of PSMP glycosylated products were altered. The internal conformational unfolding of the modified products was observed by scanning electron microscopy (SEM), indicating that the structural changes were the main reason for the functional properties of the proteins. In summary, the glycosylation of PSMP significantly improved both its structural and functional properties. This study offers new ideas and methods for the applications of PSMP, as well as some theoretical and practical support for research into the structural relationships of glycosylated proteins.